Komodifikasi Anime sebagai Budaya Populer Pada Komunitas Anime One Piece Di Kota Medan - Muhammad Irfan Syukhori Lubis (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
The development of technology and communication currently building all these things can be easily access including culture .The process of social and cultural occurring in the information revolution has become a fascinating subjects of the principle of social science for a long time .Is related to the process is a process komodifkasi cultural values change to become a value exchange .Komodifikasi cultural change culture so as to be a popular culture is very interesting .Researchers took survey areas in the community one piece id .The kind of research taken qualitative researchers is descriptive. The research data collection are, interview process observation and, documentation. Based on the research done, the anime komodifikasi as popular culture is in one piece id field community has been very good.Besides, the reciprocal existence in of the communication and the culture that emerged in communities with anime develop a community one piece id be the space for their fans anime one piece in exchanging information and spreading the culture so that people can receive the cultural. Key Word: Komodifikasi, Anime, Popular Culture